Impact of recurrent acute heart failure hospitalizations on prognosis of heart failure patients. (2nd May 2022) - Cardoso, A; Tinoco, M; Dias, G; Faria, B; Pereira, T; Fernandes, M; Almeida, F; Lourenco, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Hospitalizations for acute heart failure (AHF) are significant events for heart failure (HF) patients (pts) with each hospitalization portending a poor prognosis. Our aim was to compare pts with recurrent AHF admissions to those without and to study the impact of recurrent admissions on overall mortality. Methods: Single centre retrospective study that included all pts followed at the HF Clinic of the Cardiology Department that had at least one visit during 2018. All data since their initial follow-up on HF Clinic was considered. Recurrent admissions were defined as 2 or more admissions for AHF in the same year, during the follow-up. Results: A total of 138 pts were included (83% male, mean age 61±11years). Dilated cardiomyopathy (65;47%) and ischemic cardiomyopathy (62;45%) were the most frequent aetiologies and most pts had HF with reduced ejection fraction (131;95%). Mean left ventricular ejection fraction (LVEF) was 26±9% and right ventricular dysfunction was present in 27% of the cases. The majority of patients was on NYHA class II (80, 58%). A total of 84 (61%) pts was medicated with inhibitors of the renin-angiotensin system (iRAS), 45 (33%) with angiotensin receptor-neprilysin inhibitor (ARNI), 127 (92%) with beta-blockers (BB) and 116 (84%) with mineralocorticoid receptor antagonists (MRA). Ninety-seven (70%) pts had a cardiac electronic device implanted (47 CRT, 50 ICD). During a median follow-up of 40 months (IQR 32-58), 41 (30%) pts had hospitalizations for AHF and 21 (15%) had recurrent admissions. The median time to the first hospitalization was 16 months (IQR 6-29). Pts with recurrent admissions had a similar comorbidity profile and HF aetiology in comparison to pts with one or none admissions. Considering baseline echocardiographic parameters on first visit, they had a higher mean E/E' ratio (22±8 vs 14±6, p= .012) and pulmonary systolic artery pressures (52±20 vs 38±14 mmHg, p= .026). No differences were found in LVEF, left ventricular volumes, presence of right ventricular dysfunction or mitral regurgitation. They were less frequently medicated with iRAS or ARNI (81% vs 96%, p=.012) and BB (81% vs 94%, p= .043) and had a higher mean diuretic dosage (87±47 vs 63±43 mg). During the follow-up a total of 31 (22%) pts died, 14 (10%) for cardiovascular reasons. Pts with recurrent AHF admissions were more likely to die from any cause (log rank =.01). On a multivariate analysis, recurrent AHF hospitalizations were an independent predictor of all-cause death (HR 2.4, IC95% 1.1-5.2, p=.03). Conclusion: Recurrent AHF hospitalizations are associated with a worse long-term outcome of HF pts. Efforts should be made for an earlier identification of these pts. A higher baseline pulmonary systolic artery pressure and mean E/E' ratio may identify a higher risk group who benefits from a closer follow-up.